2006
DOI: 10.1111/j.1432-0436.2006.00054.x
|View full text |Cite
|
Sign up to set email alerts
|

A role for chromosomal protein HMGN1 in corneal maturation

Abstract: Corneal differentiation and maturation are associated with major changes in the expression levels of numerous genes, including those coding for the chromatin-binding high-mobility group (HMG) proteins. Here we report that HMGN1, a nucleosome-binding protein that alters the structure and activity of chromatin, affects the development of the corneal epithelium in mice. The corneal epithelium of Hmgn1 −/− mice is thin, has a reduced number of cells, is poorly stratified, is depleted of supra-basal wing cells, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 64 publications
(90 reference statements)
3
28
0
Order By: Relevance
“…Thus, Klf4 appears to be an integral part of the genetic network that regulates the fine balance between cell proliferation and stratification at the ocular surface. Our re- sults, taken together with other reports, demonstrate that the structural integrity of the corneal epithelium is governed by a complex set of transcription factors, such as KLF4, Pax6, and AP-2␣ (20,23,59,60,72) as well as chromosomal protein HMGN1 (8). It is surprising that in spite of multiple abnormalities associated with the Klf4CN ocular surface in the mouse, the human KLF4 locus has not yet been associated with any ocular dystrophies.…”
Section: Discussionsupporting
confidence: 67%
“…Thus, Klf4 appears to be an integral part of the genetic network that regulates the fine balance between cell proliferation and stratification at the ocular surface. Our re- sults, taken together with other reports, demonstrate that the structural integrity of the corneal epithelium is governed by a complex set of transcription factors, such as KLF4, Pax6, and AP-2␣ (20,23,59,60,72) as well as chromosomal protein HMGN1 (8). It is surprising that in spite of multiple abnormalities associated with the Klf4CN ocular surface in the mouse, the human KLF4 locus has not yet been associated with any ocular dystrophies.…”
Section: Discussionsupporting
confidence: 67%
“…1C) and ubiquitously detected in most tissues (6). Furthermore, while the expression of HMGN1 and HMGN2 is generally downregulated during differentiation (4,13,18), our preliminary analyses indicate that HMGN3 protein is first expressed in a few pancreatic cells only after embryonic day 14.5 and the levels of the protein increase during differentiation (data not shown). HMGN3 is highly expressed in the terminally differentiated ␤ cells of both mice and humans.…”
Section: Discussionmentioning
confidence: 73%
“…The overexpression experiments afforded the opportunity to test the mutant HMGN1 proteins for their abilities to impact es- (56,58). Furthermore, this mutant is unable to rescue a number of phenotypes associated with hmgn1 Ϫ/Ϫ mouse embryonic fibroblasts (MEFs) (6,7,42,43,63), a finding which previously suggested that the two substitution mutations abolish the biological activity of HMGN1. Unexpectedly therefore, the effect of the HMGN1 S20E/S24E mutant upon estrogen stimulation differed depending on the target gene.…”
Section: Resultsmentioning
confidence: 99%
“…on March 21, 2019 by guest http://mcb.asm.org/ esis (6), development (8,35,48), and differentiation, in which its level is tightly regulated and progressively diminished (4,7,33,39,50,52,53). Its effect on estrogen-mediated transcriptional regulation suggests that HMGN may also be involved in the in vivo physiology of estrogen action, which requires further exploration.…”
Section: Discussionmentioning
confidence: 99%